Manajemen Kurikulum dalam Membina Kompetensi Intelektual, Etis, dan Pengembangan Diri Peserta Didik di MA Darul Falah Batu Putu Bandar Lampung - Agung Fahri; Nirva Diana; M. Kharis Fadhilah (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This study aims to analyze curriculum management in fostering students’ intellectual, ethical, and self-development competencies at MA Darul Falah Batu Putu Bandar Lampung. Employing a qualitative evaluative case study design, the research involved purposively selected informants, including the head of the madrasah, vice principal for curriculum affairs, teachers, activity supervisors, and students. Data were collected through in-depth interviews, observation, and document analysis, and were analyzed through data condensation, data display, and conclusion drawing, with source and technique triangulation used to strengthen data credibility. The findings reveal that curriculum management at MA Darul Falah is implemented through the integration of intracurricular learning, religious habituation, madrasah culture, co-curricular activities, and extracurricular programs. Curriculum planning is directed toward aligning academic achievement, Islamic values, character formation, discipline, independence, and students’ potential development. Curriculum implementation indicates that intellectual competence is fostered not only through mastery of subject matter but also through literacy development, academic assignments, and active student engagement. Ethical competence is cultivated through religious routines, teacher role modelling, school regulations, and a religious institutional culture, while self-development competence is strengthened through student organizations, extracurricular activities, social programs, and leadership development. However, the evaluation of ethical and self-development competencies still requires more systematic instruments, such as attitude assessment rubrics, student development portfolios, homeroom teacher journals, and data-based program evaluation. The study concludes that the curriculum of Islamic boarding school-based madrasahs should be understood as a holistic development system that integrates students’ academic, moral, spiritual, and personal dimensions. The implication of this study is that madrasahs need to develop more measurable, well-documented, and data-informed curriculum management so that educational success is assessed not only through academic achievement but also through students’ character formation, independence, leadership, and readiness to participate in broader social life.